2020
DOI: 10.1016/j.bjid.2020.04.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: a meta-analysis of diagnostic test accuracy of commercial assays registered in Brazil

Abstract: The accuracy of commercially available tests for COVID-19 in Brazil remains unclear. We aimed to perform a meta-analysis to describe the accuracy of available tests to detect COVID-19 in Brazil. We searched at the Brazilian Health Regulatory Agency (ANVISA) online platform to describe the pooled sensitivity (Se), specificity (Sp), diagnostic odds ratio (DOR) and summary receiver operating characteristic curves (SROC) for detection of IgM/IgG antibodies and for tests using naso/oropharyngeal swabs in the random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
20

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 6 publications
(3 reference statements)
4
108
1
20
Order By: Relevance
“…Additional methods, such as serological tests, in which the virus antigens or antibodies produced are investigated, can also confirm the diagnosis 6,7 . Large-scale testing, rapid diagnosis, and immediate case isolation, associated with rigorous screening and preventive measures of social distance, and basic hygiene, are essential procedures to reduce the spread of COVID-19 1,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional methods, such as serological tests, in which the virus antigens or antibodies produced are investigated, can also confirm the diagnosis 6,7 . Large-scale testing, rapid diagnosis, and immediate case isolation, associated with rigorous screening and preventive measures of social distance, and basic hygiene, are essential procedures to reduce the spread of COVID-19 1,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This was corroborated by a Brazilian study that analyzed the rapid tests available in the country and found them to be efficacious. 30 In this study this was important for laboratory confirmation of C02, C03, C04 and C05.…”
Section: Discussionmentioning
confidence: 95%
“…Hoffman et al (2020) evaluated RDT #3 and found higher speci cities, 100% for IgM and 99.2% for IgG. A meta-analysis of regulatory data from serologic RDTs approved in Brazil found a pooled speci city of 97% for IgM and 98% for IgG (Castro et al, 2020). A study evaluating a RDT in China included 128 "clinical negative samples" and found one sample positive for IgG and 10 positive for IgM (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%